2006
DOI: 10.1136/bjsm.2005.024521
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards exercise and physical activity behaviours in Greek schoolchildren after a year long health education intervention

Abstract: Objective: To examine the short term effects of a health education programme on Greek primary schoolchildren Methods: The school based intervention programme was applied to 29 children in the 6th grade of the 2nd Primary School of Agios Stefanos (,12 000 inhabitants); 49 pupils from the 1st Primary School constituted the control group. To assess the effectiveness of the intervention, attitude and behavioural variables were measured before and after the intervention. Results: After adjustment for initial differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 29 publications
(15 reference statements)
6
73
0
3
Order By: Relevance
“…Few other intervention studies report significant changes such as these after such limited exposure. The majority of these studies demonstrate changes as a result of interventions lasting in the region of a year for cardiovascular fitness 18 and psychosocial measures, 19 but sometimes up to 3 years for psychosocial variables. 20 Limitations of this study include the lack of rigorous monitoring data to support the evaluation, limited data collected from control schools, and the small number of learners tested at control schools.…”
Section: Discussionmentioning
confidence: 99%
“…Few other intervention studies report significant changes such as these after such limited exposure. The majority of these studies demonstrate changes as a result of interventions lasting in the region of a year for cardiovascular fitness 18 and psychosocial measures, 19 but sometimes up to 3 years for psychosocial variables. 20 Limitations of this study include the lack of rigorous monitoring data to support the evaluation, limited data collected from control schools, and the small number of learners tested at control schools.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13]15,18,28 Four of the eight studies that reported intervention effects on self-efficacy reported significant improvements in that construct; [14][15][16]18 however, only two out of six interventions reported significant improvements in physical activity enjoyment or preference. 22,27 Positive effects on attitudes towards physical activity, 24,28 perceived social support for physical activity, 18 outcome expectancies, 16 and exercise behavioural capability 14 were also reported.…”
Section: Resultsmentioning
confidence: 99%
“…The most common theoretical framework applied was the Social Cognitive Theory (13 studies). [10][11][12][13][14][15][16][17][18][19][20][21][22][23] Only two studies reported using the Theory of Planned Behaviour, 13,24 with other theoretical frameworks, such as the Behavioural Choice Theory, 11 the Organizational Change Theory, 14 the Social Ecological Model, 25 and Pender's Health Promotion Model 23 being reported by single studies. Four interventions did not explicitly identify using a theoretical framework; [26][27][28][29] however, the effects on theoretically derived constructs such as knowledge and beliefs, enjoyment, social influences, barriers, perceived health, and self-efficacy were reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the important predictors of people engaging in physical activity is attitude towards exercise [7]; in particular children will participate in physical activities when they have a positive attitude towards physical activity [14]. Several studies have shown that integrating health education in classes, labs and readings can have positive impact on children's health attitude [5,12]. However, many schools (particularly in the U.S.) intend to improve students' academic scores by increasing time for core curricular subjects and decreasing physical education (PE) [36], or other scheduled physical activity.…”
Section: Attitudes About Physical Activitymentioning
confidence: 99%